Fatores associados ao uso de medidas de proteção pessoal contra as arboviroses por mulheres em idade fértil moradoras em Fortaleza-Ceará - Dias, Livia Karla Sales (2022)
Arboviruses are a serious public health problem in Brazil and in many countries around the world. Recommendations for the use of personal protection measures against arboviruses were intensified and aimed mainly at pregnant women and women of childbearing age, since the Zika virus epidemic. The study aims to analyze the factors associated with the use of personal protection measures against arboviruses in a cohort of women of childbearing age living in Fortaleza-Ceará. Cohort carried out in two waves, between 2018 and 2019, with sexually active women aged 15 to 39 years, living in the city of Fortaleza, Ceará, Brazil. Participated in 1173 users of four basic health units who registered high rates of Chikungunya in 2017. A semi-structured questionnaire was applied using the Survey Monkey software that addressed questions about socioeconomic, environmental and health factors, sexual and reproductive health, knowledge and behavior about arboviruses, means information and personal protection measures. Three analysis outcomes were selected: use and non-use of repellent, protective screen, mosquito net, long clothing, insecticide and condom; quantitative use of personal protection measures (used one personal protection measure/used two or more measures/not used personal protection measure); use of individual repellent (continued use of repellent/discontinued use of repellent/no use of individual repellent). For the dichotomous outcome, Logistic Regression Analysis was used and for the outcomes with three categories, the Multinomial Logistic Regression Analysis. Odds ratio (OR) values and respective Confidence Intervals of 95% (95%CI) are presented. Odds ratio (OR) values and respective Confidence Intervals of 95% (95%CI) are presented. It was identified that the use of individual repellent as a personal protection measure by women of childbearing age, since the ZIKV epidemic, was strongly related to higher education (OR=2.78; 95%CI:1.49–5, 19) and pregnancy when it occurred after the Zika virus epidemic period (OR=2.76; 95%CI:1.81–4.22). In addition, behavioral changes in the face of the Zika virus epidemic (OR =3.76; 95%CI:2.35–6.00), employability (OR=1.79;95%CI:1.13–2.85) and information received by health professionals (OR=1.39; 95%CI: 1.01–1.90) and the media (OR=1.47; 95%CI: 1.04–2.08) had repercussions on the use of repellent individual during the cohort. On the other hand, the non-recognition of the importance of the measure and the cost linked to the product justified the reasons for not using repellent. Repellent and insecticide were the most used measures, while condoms and protective mesh had less adherence, in descending order. The final model of the multinomial outcome showed that higher education and pregnancy increased the risk ratio for the use of two or more measures by two times. Having a partner (OR=1.60; 95%CI:1.11–2.28); not depending on social benefits (OR=1.58; 95%CI:1.07–2.33), knowing about the transmission of arboviruses (OR=1.55; 95%CI:1.03–2.31), receiving guidance from health professionals (OR=1.88; 95%CI:1.29–2.75) and television (OR=1 .87; 95%CI:1.27–2.76), talking to friends about Zika (OR=1.94; 95%CI:1.31–2.88) were positive for using more personal protection measures. We concluded that the recommendation to use personal protection for arboviruses produced some effect among women with higher education, greater economic resources and among pregnant women. During the Zika epidemic, the pregnant women received the repellent as a protection measure, in addition to guidelines professionals and the media, strengthening this adhesion. It is necessary to formulate public policies and offer guidelines that are understandable and that serve vulnerable populations and specific groups so that access and effective adherence to the recommended measures for the population is possible.